(untitled) - PUTU KRESNAYANA MAHARDIKA, I (Jurnal Ilmu Manajemen (JIM), 2017)
Indonesian Stock Exchange separate the trade board into main board and development board, aiming so that investor can differ risk factor that occur. The purpose of this study is knowing the influence of profitability, asset structure, growth, NDTS toward capital structure, and the differences all on the main board and development board. Main board and development board period 2011-2015 is the object of this study. Sample used in this study are 45 companies in each trade board which selected by simple random sampling method. This Study using causal associative approach which use secondary data obtained from the documentation. Multiple regression linear is the analysis method used. The result shows that profitability and asset structure negatively impact on capital structure company’s main board and development board. Growth has no impact to capital structure at main board and development board. NDTS at main board negatively impact to capital structure, while at development board is positively impact to capital structure. Difference test results independent t-test shows no difference between profitability, asset structure, NDTS, and capital structure at main board and development board, While the growth on the main board and development board differences. Different capital structures also show that firm size has no effect on capital structure. Recommendations from this study is company need to consider profitability, asset structure, growth, non-debt tax shield in company’s capital structure. For investor, no need to confuse investing at all trade market, because both of them have the same risk if seen from the company’s debt risk. Keywords: capital structure, profitability, asset structure, growth, non-debt tax shield